Flexibility in partitioning strategies of fourth graders - Yeliz Yazgan (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
This study combines the concepts of flexibility and partitioning, and aims to probe fourth grade students’ flexibility in partitioning strategies. Seven students participated in this descriptive case study. Students were given three partitioning tasks. Forty-eight answers produced by students were evaluated and classified based on the strategies defined in the taxonomy developed by Charles and Nason (2000). Results showed that students could easily change their strategies both within and across tasks. Namely, they displayed both inter- and intra-task strategy flexibility to a large extent even though they did not have any intervention on partitioning. Another point that findings have implicated was that the fourth graders’ flexibility in partitioning strategies may be utilized to introduce concepts of equivalent fractions and mixed numbers. Results are discussed in terms of their implications related to mathematics education, and some recommendations aimed at learning environments and future studies are presented.